The objective and perceived built environment: What matters for happiness?. Issue 1 (2nd January 2017) - Kent, Jennifer L.; Ma, Liang; Mulley, Corinne
Abstract: Subjective well-being, or a positive evaluation of one's own life, is an important component of human health. The concept is regularly used as a policy measure for social progress, with proponents promoting the idea of the 'happy city'. But empirical research on ways to nurture subjective well-being through urban planning remains limited. Previous relevant research has considered the impact of specific aspects of the built environment on components of subjective well-being, but a gap exists in literature on the exploration of multiple built environment effects on multiple components of subjective well-being. This study fills this gap. It presents a quantitative analysis of results from a survey of 562 households in Sydney, Australia. The relative influence of objective and perceived built environment variables are analysed with multiple elements of subjective well-being to show a more comprehensive picture of the impacts of place on subjective well-being. We found perceived evaluations of built environment characteristics were more often associated with subjective well-being, with perceptions of aesthetics and community cohesion particularly important. The paper concludes with recommendations for policy and research, including the need to incorporate perceived measures of built environment and health variables in analyses of links between built environments and health.